Use of Biochar as an Amendment for Remediation of Heavy Metal-Contaminated Soils：Prospects and Challenges - LAHORI, Altaf Hussain; GUO, Zhanyu; ZHANG, Zengqiang; LI, Ronghua; MAHAR, Amanullah; AWASTHI, Mukesh Kumar; SHEN, Feng; SIAL, Tanveer Ali; KUMBHAR, Farhana; WANG, Ping; JIANG, Shuncheng (Pedosphere, 2017)
Biochar（BC）, known as the new black gold, is a stable, novel carbonaceous by-product that is synthesized through pyrolysis of biological materials in the absence of O_2.Recently, an emerging interest in the application of BC as a robust soil amendment has given rise to a broad research area in science and technology.It is considered a promising remediation option for heavy metal（HM）-contaminated soils to reduce HM bioavailability to plants.Remediation efficacy of BC depends on the porosity, composition,pyrolysis temperature, feedstock, and residence time of pyrolysis.This review article aimed to present an overview of BC use in the immobilization of HMs, i.e., Cd, As, Pb, Zn, Ni, Cu, Mn, Cr, and Sb, in contaminated soils.The remaining uncertain factors, including the specific soil HM immobilization mechanisms, long-term beneficial effects, and potential environmental risks associated with BC application are analyzed.Future research must be conducted to ensure that the management of environmental pollution is in accord with ecological sustainability and adaptation of the black gold biotechnology on a commercial basis for immobilization of HMs in contaminated soils.